Bioactive Pigments of Monascus purpureus: Identification and Characterization - Shaleha, Resha Resmawati; Yuliana, Anna; Rahmiyani, Ira; Pebiansyah, Anisa; Indriyanti, Indriyanti (Journal of Food and Pharmaceutical Sciences, 2025)
Monascus purpureus is a filamentous fungus that has long been recognized as one of the main producers of natural pigments. These pigments, including yellow (ankaflavin, monascin), orange (rubropunctatin, monascorubrin), and red (rubropunctamine, monascorubramine), are widely used as natural coloring agents. Compared to synthetic dyes, Monascus pigments are considered safer and possess additional biological activities, making them attractive for applications in the food, pharmaceutical, and cosmetic industries. Therefore, accurate identification of the pigments in Monascus purpureus is essential to ensure their safety, functionality, and potential industrial applications. The aim of this research is to determine the results of pigment identification Monascus purpureus using UV-Vis Spectrophotometry, Fourier Transform Infra-Red (FTIR), Thin Layer Chromatography (TLC), Preparative Thin Layer Chromatography (Preparative TLC), and Liquid Chromatography- Mass Spectrometry (LC-MS). The method used is method laboratory experiments. Samples are tested using several instruments. The extraction results show that the % yield value meets the requirements, namely >10%, then the fractionation results show that the water fraction gets more thick extract, the TLC results for the water fraction show a spot height of 4.7 cm with a value of Rf 0.78, the results of Preparative TLC on the water fraction show the presence of a single fluorescent band at wavelengths of 254 nm and 366 nm. The UV-Vis spectrophotometry results were identified at a wavelength of 477 nm with an absorbance of 0.364, then the FTIR results on Preparative TLC scrapings from the water fraction showed the presence of functional groups from the orange pigment structure and the LC-MS results showed that the sample was a compound. Monascorubrin (C23H28O5) with a molecular weight of 384.99 g/mol and compound rubropunctatin (C21H22O5) with a molecular weight of 354.74 g/mol. These results provide information that the sample is an orange pigment from Monascus purpureus with two compounds monascorubrin and rubropunctatin.